A multi‐faceted approach to analyzing glucose heat‐degradants and evaluating impact to a CHO cell culture process. Issue 9 (6th July 2020) - Moore, Brandon; Grinnell, Chris; Boumajny, Boris; Chen, Rachel; Frenkel, Ruth; de Vilmorin, Phil; Sosic, Zoran; Khattak, Sarwat
Abstract: Glucose solutions are commonly heated before use in medical and biotech applications to maintain cleanliness, however the resulting degradants can be toxic. This study examines two approaches to evaluating the heat degradants resulting from holding a 40% glucose solution at 55°C for 5 weeks: first, chemical changes to the solution were identified and quantified via analytical testing, and second the toxicity of the heat‐degraded 40% glucose solution was evaluated empirically by using it as a feed stock for a fed‐batch CHO‐cell‐based protein therapeutic manufacturing process. Colorimetric analysis quantified a color change during heating, and liquid chromatography assays measured an increase in the concentrations of two unknown degradants along with the commonly identified glucose impurity 5‐hydroxymethylfurfural (5‐HMF). Solution pH decreased over time, corresponding with an increase in formic acid concentration as measured via GC–MS. Despite this, cell culture toxicity was not observed, and protein productivity and product quality were maintained.